Pengaruh Kepemimpinan Melayani Terhadap Motivasi Bawahan Dalam Melayani Publik: Peran Mediasi Personaliti Agreeableness (Studi Pada Organisasi Publik Di Indonesia) - Diah Astrini Amir; Muhammad Afif Sallatu (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2022)
This study aims to reveal the influence of servant leadership on the motivation of subordinates in serving the public. This study examines the direct or indirect effect by examining the potential mediating role of agreeableness personality on the influence of servant leadership on the motivation of subordinates in serving the public. A total of 132 respondents participated in filling out the questionnaire. However, only 108 respondents' data were eligible for further testing. This study uses non-probability sampling with purposive sampling technique, namely by determining the criteria for respondents who work in public organizations in Indonesia, have worked for one year in the organization, and have worked together with their superiors for at least one year. Hypothesis testing was done by mediated regression analysis with the help of SPSS statistical tools. These results indicate that servant leadership has a significant positive effect on the motivation of subordinates to serve the public directly and indirectly, which can be fully mediated by agreeableness personality. An explanation of the findings is presented in the discussion section.